Evaluating nutritional strategies in the sow transition period to improve sow and litter performance, colostrum yield, and piglet survivability - Gourley, Kiah Marie (Kansas State University, 2020)
Three experiments using a total of 1,325 sows were used to determine the impact of different sow feeding strategies on sow and litter performance. Experiment 1 determined the optimal soybean meal concentration in lactating sow diets using three levels of increasing dietary soybean meal (25, 30, or 35% of total diet). Increasing soybean meal concentration increased sow BW loss and tended to increase sow backfat loss from farrowing to weaning. Sow average daily feed intake (ADFI) decreased linearly as soybean meal concentration increased. Despite the linear response in ADFI, the greatest decrease was observed as soybean meal concentration increased from 30 to 35% of the diet. There was no evidence for difference in wean to estrus interval, or litter performance between dietary treatments. Sow serum urea nitrogen concentrations taken on d 14 of lactation increased as soybean meal concentration increased. Experiment 2 evaluated the duration of feeding increased Lys and energy prior to farrowing on sow and litter performance, piglet survival and colostrum quality in a commercial sow farm. Sows were fed 1 of 3 dietary regimens starting on d 107 of gestation: 1) Control: 2.0 kg/d gestation feed (12.5 g SID Lys and 6.5 Mcal ME) until d 113 of gestation, then 2.7 kg/d lactation feed (28 g SID Lys and 9.4 Mcal ME) until parturition; 2) 2.0 kg/d gestation feed (12.5 g SID Lys and 6.5 Mcal ME) until d 113 of gestation, then 3.8 kg/d lactation feed (40 g SID Lys and 13.3 Mcal ME) until parturition; or 3) 3.8 kg/d lactation feed (40 g SID Lys and 13.3 Mcal ME) until parturition. Increasing the duration of feeding additional Lys and ME increased sow weight and backfat gain from d 106 to 113. Average total born and born alive piglet birth weight (BiWt) was greater in gilts fed 3.8 kg/d lactation diet starting on d 107 or 113 vs. control, with no difference in piglet BiWt in sows or weaning weight in gilts and sows. Piglet mortality after cross-foster to weaning was decreased in sows fed 3.8 kg/d lactation diet starting on d 113 vs. control or increased lactation diet starting on d 107, but not in gilts. Litter gain from cross-foster to weaning was decreased in gilts fed 3.8 kg/d lactation diet starting on d 107 compared to control, with no evidence for difference in sows. Colostrum immunoglobulin G was increased in gilts and sows fed 3.8 kg/d of the lactation diet starting on d 113 compared to control. There was no evidence dietary regimen influenced piglet colostrum intake or colostrum yield, or subsequent reproductive performance. Experiment 3 evaluated the effects of timing and size of meals before farrowing on sow and litter performance under commercial conditions. Sows were fed 1 of 3 feeding management strategies until farrowing: 1) 2.7 kg lactation diet (1.15% standardized ileal digestible lysine and 2,153 Kcal/kg net energy) once daily at 0700 h; 2) 4 daily meals of 0.67 kg (0100 h, 0700 h, 1300 h, 1900 h); 3) ad libitum lactation diet and encouraged to consume feed at 0100 h, 0700 h, 1300 h, and 1900 h. Feeding sows ad libitum before farrowing tended to reduce sow body weight loss and reduce backfat loss from entry into the farrowing house until weaning compared to sows fed 4 daily meals, with sows fed once daily intermediate. Litter gain from 24 h to weaning tended to be greater in sows fed ad libitum or 4 times daily prior to farrowing compared to sows fed one meal. Piglet weaning weight increased in sows fed ad libitum before farrowing, compared to those fed one meal, with those fed 4 times daily intermediate. There was no evidence for difference in farrowing duration, stillborn rate, colostrum yield, or 24 h piglet survival regardless of treatment. However, from 24 h after farrowing to weaning, sows fed one daily meal prior to farrowing had an increased percentage of fall-behind pigs compared to sows fed ad libitum, and increased preweaning mortality compared to sows fed four daily meals, resulting in reduced weaned percentage compared to sows fed four daily meals. There was no difference in subsequent reproductive performance regardless of treatment.
Keywords: lactation; sow; transition period; litter performance; piglet survival